Pengaruh Model Guided Discovery Learning Berbantuan Question Card Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas VIII SMP Negeri 5 Padang - Selinda Wigati Asih Afiana; Tuti Lestari; Widia Kemala Sari; Fatma Wati (Al-Alam: Islamic Science Education Journal, 2026)
Critical thinking skills are essential competencies that need to be enhanced in science learning. This study aims to determine the effect of the Guided Discovery Learning model assisted by Question Cards on students’ critical thinking skills. This research employed a quantitative approach with a quasi-experimental method using a non-equivalent control control group design. This sample was selected through purposive sampling. The results showed that the implementation percentage was 83% for teacher and 78% for students. In addition, the results of the student response to the implemented learning of 79,41%, suggesting a positive response to the calculated t-value was greater than t-table value (3.65>1.99. These results indicate that is rejected and is accepted, meaning that the Guided Discovery Learning model assisted by Question Cards has a significant effect on students’critical thinking skills at SMP Negeri 5 Padang.